Evolución del conocimiento físico - García Barneto, A.; Barrios Arias, V. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1993)
In this paper we wish to present the evolution of the structure of the physic knowledge from the level of 1st year BUP to science graduates. The reliability of the responses also analysed.